ADULT TETANUS, DIPHTHERIA, AND PERTUSSIS VACCINATION AND INCIDENT DEMENTIA. (20th December 2022) - Scherrer, Jeffrey; Salas, Joanne; Wiemken, Timothy; Jacobs, Christine; Morley, John; Hoft, Daniel
Abstract: Adult vaccinations may reduce risk for dementia. We determined whether tetanus, diphtheria, pertussis (Tdap) vaccination is associated with lower risk for dementia. Analysis conducted with Veterans Health Affairs (VHA) administrative medical record data and replicated in private sector medical claims data. Patients were ≥65 years of age and free of dementia for 2 years prior to index date. Tdap vaccination in 2011 or 2012. Follow-up through 2018. Controls had no Tdap vaccination for the duration of follow-up. After controlling for confounding, patients with, compared to without Tdap vaccination, had a significantly lower risk for dementia in both cohorts (VHA: HR=0.58; 95%CI:0.54 - 0.63 and MarketScan: HR=0.58; 95%CI:0.48 - 0.70). Results were replicated in two cohorts with different clinical and sociodemographic characteristics. Several vaccine types are linked to decreased dementia risk, suggesting that these associations are due to nonspecific effects on inflammation rather than vaccine-induced pathogen-specific protective effects.